NCREASE OF CAVITATION RESISTANCE OF SECONDARY SILUMINS - A. A. Mitjaev; S. B. Belikov; V. N. Povzlo (Литьë и металлургия)
The structure, mechanical characteristics and cavitation resistance of secondary silumins after refining and combined refiner-modificating processing is investigated. The improvement of mechanical characteristics and cavitation resistance as a result of the structure decomposition is received.